Assessing the Link Between Intimate Partner Violence in Pregnancy and Stillbirths [1F]. (May 2016) - Khatlani, Khaula; Azam, Iqbal; Baqir, Muhammad; Mehmood, Amber; Duke, Cindy; Pasha, Omrana
Abstract : INTRODUCTION: Data on the relationship between intimate partner violence (IPV) during pregnancy and stillbirths is scarce. We aimed to determine the association of stillbirths and IPV during pregnancy in Pakistan. METHODS: Using 1:2 case-control ratio, 256 cases (women with stillbirths) and 539 controls (women with live births) were selected from the Global Network for Women's and Children's Health Research Registry in Pakistan and individually matched on parity in a matched, case-control community-based study. Data was collected between February and May 2014, using WHO questionnaire to determine IPV. Multivariable conditional logistic regression model assessed the association between IPV in pregnancy and stillbirths, while adjusting for women's education, working status, prior stillbirths, major antepartum hemorrhage, hypertensive disease, fetal malpresentation, obstructed/prolonged labor, severe pre-eclampsia/eclampsia, birth attendant and mode of delivery. RESULTS: Maternal age was an effect modifier for the association of physical and psychological IPV in pregnancy with stillbirths. In the adjusted analyses, the odds of experiencing physical IPV during index pregnancy was 4 times more among women 25–34 years, delivering stillbirths, than those delivering live births (Matched adjusted odds ratio [MAOR]=4.1 [95% CI 1.5–11.2]). A negative association was detected between psychological IPV and stillbirths among women younger than 25 years (MAOR=0.2 [95% CI 0.03–0.9]). A statistically significant association was not observed between sexual IPV during pregnancy and stillbirths. CONCLUSION: Mid-reproductive age women delivering stillbirths, are more likely to experience physical IPV in pregnancy. This calls for screening of women for violence during their antenatal visits.